2017
DOI: 10.22605/rrh4014
|View full text |Cite
|
Sign up to set email alerts
|

Use of cell phones and computers for health promotion and tobacco cessation by American Indian college students in Montana

Abstract: A B S T R A C TIntroduction: Cell phones and personal computers have become popular mechanisms for delivering and monitoring health information and education, including the delivery of tobacco cessation education and support. Tobacco smoking is prevalent among American Indians (AIs) and Alaska Natives (ANs), with 26% AI/AN adult men smoking compared to 19% of Caucasian adult males and 22% of African American adult males. Smoking is even more prevalent in Northern Plains AI populations, with 42% of men and wome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…Participants completed these measures through a secure online survey system which can be accessed on smartphones or computers, depending on their preference. Participants were also asked to identify a quit date within 30 days of signing the consent form, similar to earlier reported STOMP protocols [ 22 ]. All subsequent data collection was through their personal mobile phones or computers.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Participants completed these measures through a secure online survey system which can be accessed on smartphones or computers, depending on their preference. Participants were also asked to identify a quit date within 30 days of signing the consent form, similar to earlier reported STOMP protocols [ 22 ]. All subsequent data collection was through their personal mobile phones or computers.…”
Section: Methodsmentioning
confidence: 99%
“…We previously reported that among AIs living in rural communities, similar to the regions included in the current study, 86% owned a cellphone. Of these, 93% had unlimited texting and 80% had internet access [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…These qualitative and survey-based needs assessments strongly suggest that Indigenous adults have interest in technology-based health education resources, confidence to use (or learn how to use) these resources, and desire to be involved in development of such resources. 54,55,[57][58][59]73,82 In two needs assessment studies, Indigenous adults were resistant to technology-based health education and support-one specific to AI/ AN cancer survivors who strongly preferred face-to-face support 36 and one in which AI/ AN veterans were resistant to remote-access health education/ support but eventually warmed to the idea as their concerns were addressed. 31 As with all health education programs and resources, engaging the intended Indigenous community early in program development will increase the program's acceptability and usability among the priority audience.…”
Section: Discussionmentioning
confidence: 99%
“…[109,110] Smartphone ownership appears to cross socioeconomic boundaries [111], with studies showing ownership amongst homeless adults, rural communities, Indigenous populations, low-income adults and the elderly on the rise. [108,[112][113][114] Some data suggests that homeless adults over 18 years in major cities in Australia are more likely to own a smartphone than Australians generally, taking advantage of free Wi-Fi hotspots and internet access in public libraries to reduce costs and stay connected. [115] Compared to mobile phone owners, smartphone owners are more diverse in terms of age, household income and education levels.…”
Section: Innovative New Technologymentioning
confidence: 99%